Evaluation of attention in APP/PS1 mice shows impulsive and compulsive behaviours. (8th July 2019) - Shepherd, Amy; May, Carlos; Churilov, Leonid; Adlard, Paul A.; Hannan, Anthony J.; Burrows, Emma L.
Abstract: While Alzheimer's disease (AD) is traditionally associated with deficits in episodic memory, early changes in other cognitive domains, such as attention, have been gaining interest. In line with clinical observations, some animal models of AD have been shown to develop attentional deficits, but this is not consistent across all models. The APPswe/PS1ΔE9 (APP/PS1) mouse is one of the most commonly used AD models and attention has not yet been scrutinised in this model. We set out to assess attention using the 5‐choice serial reaction time task (5CSRTT) early in the progression of cognitive symptoms in APP/PS1 mice, using clinically translatable touchscreen chambers. APP/PS1 mice showed no attentional changes across 5CSRTT training or any probes from 9 to 11 months of age. Interestingly, APP/PS1 mice showed increased impulsive and compulsive responding when task difficulty was high. This suggests that while the APP/PS1 mouse model may not be a good model of attentional changes in AD, it may be useful to study the early changes in impulsive and compulsive behaviour that have been identified in patient studies. As these changes have not previously been reported without attentional deficits in the clinic, the APP/PS1 mouse model may provide a unique opportunity to study these specific behavioural changes seen in AD, including their mechanistic underpinnings and therapeutic implications. Abstract : APP/PS1 mice show more impulsive and compulsive behaviour compared to WTs when attention was taxed in the 5‐choice serial reaction time task.